Determinants of Bank XZ'S Corporate Value: Liquidity, Leverage, and Profitability - Kharis Yuwono Mardhi; Dito Rinaldo (Oikonomia : Journal of Management Economics and Accounting, 2026)
This study aims to determine the influence of liquidity and leverage on the company's value through profitability in bank "XZ" for a predetermined research period. The independent variables in this study are liquidity and leverage, the intervening variable is profitability, while the dependent variable is the company's value. The research method used is a descriptive and verifiable method with a quantitative approach. The data analysis techniques used include descriptive statistical analysis, linear regression analysis, t-test, F-test, and multiple regression analysis. The data used is secondary data obtained from the financial statements of the "XZ" bank. The results of the study show that liquidity has a negative and insignificant influence on profitability. Leverage has a positive but insignificant effect on profitability. Simultaneously, liquidity and leverage have no significant effect on profitability. Profitability has a negative effect on the value of the company. Liquidity and leverage also have a negative and insignificant effect on the value of the company. In addition, liquidity and leverage simultaneously do not have a significant effect on the value of the company through profitability.